PENELITIAN DASAR TERHADAP MOTIVASI MAHASISWA YANG MEMILIH KEAHLIAN PENDIDIKAN BAHASA JEPANG - Kobari, Natsumi (Jurnal Pendidikan Bahasa dan Sastra, 2014)
Indonesia University of Education (UPI) takes an important role and responsibility in teachers' training of Japanese language education which is popular at senior high school in Indonesia. UPI is supposed to provide with training regularly to generate qualified Japanese language teachers. Even so, it is seen a significant difference among students in terms of the motivation toward learning Japanese language education and the effort to acquire title for being Japanese language teachers. This research aims to know the motivation of Japanese Education Study Program's students through analysis of the open-ended questionnaire survey result. From the coding result acquired, it was discovered that the majority of the students who were motivated to choose Japanese Education Study Program were influenced by their interest in Japanese language itself, and this interest is affected by the presence of an interest in pop culture and their learning experience in senior high school. In addition, 33% of all the students are considering becoming a Japanese language teacher as one option, which is less than the ones who are considering finding a job as not Japanese language teacher. Also, more than 50% of all the students want to continue their study to the higher level, i.e. master degree.